2018
DOI: 10.1177/1078155218807748
|View full text |Cite
|
Sign up to set email alerts
|

Clinical oncology pharmacist: Effective contribution to patient safety

Abstract: Management and prevention of problems related to oncology drugs are particularly important due to the excessive cost, high toxicity, and narrow therapeutic index of the antineoplastic drugs, in addition to the patients' state of health. Therefore, the presence of the pharmacist as a member of the multidisciplinary team is essential to contribute to patient safety. In this work, the interventions performed were identified, quantified, and classified to characterize the work of the clinical oncology pharmacist. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
30
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(34 citation statements)
references
References 25 publications
(42 reference statements)
1
30
1
2
Order By: Relevance
“…13 The most common error was dose-related with 79 (22.83%) cases of overdosing. However, the current prevalence is much higher compared to the finding of a study in Brazil that reported a prevalence of 6.24% 14 as well as another study in France that documented prevalence at 5.2%. 15 These differences are probably because of the better health care systems and lower prescriber or nurse to patient ratio in middle income and high-income countries compared to our study that was conducted in a low-income country.…”
Section: Discussioncontrasting
confidence: 63%
See 1 more Smart Citation
“…13 The most common error was dose-related with 79 (22.83%) cases of overdosing. However, the current prevalence is much higher compared to the finding of a study in Brazil that reported a prevalence of 6.24% 14 as well as another study in France that documented prevalence at 5.2%. 15 These differences are probably because of the better health care systems and lower prescriber or nurse to patient ratio in middle income and high-income countries compared to our study that was conducted in a low-income country.…”
Section: Discussioncontrasting
confidence: 63%
“…Our study also revealed that prescription errors were the most common error type, a finding similar to previous studies conducted in the United States, 17 Spain, 18 and Brazil. 14 The high frequency of errors during the prescription process could be due to the shortage of oncology specialists to supervise the prescription process. The absence of updated specific cancer treatment protocols for individual patient files, accompanied by inadequate continuous training of prescribers on efficient use of protocols, could also have led to increased error occurrence during prescriptions.…”
Section: Discussionmentioning
confidence: 99%
“…There are several publications highlighting the role of the clinical pharmacist in oncology. 69 This role was previously described in the USA in 1981. 10 In 1996, Oncology Pharmacy was recognized as a specialty by the US Board of Pharmaceutical Practices.…”
Section: Introductionmentioning
confidence: 85%
“…Studies conducted globally have confirmed the benefit of the integration of the OPT as part the MHT within a variety of settings in improving overall patient care. 2252…”
Section: Contributions To Patient Carementioning
confidence: 99%